Structural and phylogenetic comparisons of the complete mitochondrial genomes among taxa in genus Toona - Yan-Wen Lv; Zi-Yun Wang; Zi-Han He; Yu Xiao; Chao Wu; Xin-Sheng Hu (Scientific Reports, 2025)
Abstract Toona is of a high economic value and has a great potential for industrial and medicinal utilization. Currently, the mitochondrial genome information of this genus is incomplete. Here we sequenced the mitochondrial genomes of T. rubriflora and T. microcarpa, and re-sequenced four varieties of T. ciliata. The mitochondrial genome of T. rubriflora was 653,710 bp in length, with a typical circular structure and the GC content of 45.42%. The mitochondrial genome of T. microcarpa was successfully assembled in two circulars, designated as chromosome 1 and chromosome 2, respectively. Chromosome 1 had 474,320 bp and its GC content was 45.37%. Chromosome 2 had 166,958 bp and its GC content was 46.64%. Comparative analyses of Toona mitochondrial genomes revealed that species were highly conserved in GC content, coding gene sequences and codon usage frequency. Mononucleotide repeats were the dominant type of genome repeats. Small differences existed among species in RNA editing sites, intracellular genome homology between mitochondrial and chloroplast genomes and between mitochondrial and nuclear genomes. Most protein coding genes (PCGs) were under purifying selection. Species in Toona were relatively recently divergent, and the varieties of T. ciliata were well genetically mixed. Overall, this study provided comprehensive information on Toona mitochondrial genomes, which could be used for species identification and molecular studies on Toona.